Simulace technologií pro termické zpracování odpadu - Venhoda, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Diplomová práce se zabývá termickým zpracováním odpadu, tedy spalovnami nebezpečného odpadu a energetickým využitím komunálního odpadu, jejich popisem a analýzou legislativních podmínek. Pomocí vytvořených výpočtových modelů spalovacích jednotek posuzuje dle hmotnostních a energetických bilancí vliv systému čištění spalin a různých provozních režimů na produkci energie. Na tomto základu jsou porovnány produkce energie z termického zpracování nebezpečného a komunálního odpadu.

This thesis mainly deals with the thermal treatment of waste - hazardous waste incineration and energy recovery municipal waste incinerators - their descriptions and analysis of legislative conditions. The flue gas cleaning system energy production in different operating modes is assessed by energy and mass balances. Computational models are developed for this purpose. On this basis, productions of energy from thermal treatment of hazardous and communal waste were compared.
Simulation of technologies for thermal treatment of waste
Keywords: Energetické využití odpadu; čištění spalin; spalování odpadů; simulační model; Energy recovery of waste; flue gas cleaning; incineration of waste; simulation model